Diferenciais de rendimentos por gênero: uma análise dos efeitos composição e estrutura salarial no Brasil (1976, 1987, 1996 e 2009) - Meireles, Debora Chaves (2014)
This study aims to analyze the income differentials by gender in Brazil, in the years 1976, 1987, 1996 and 2009. Specifically, there are two objectives. First, attempt to analyze the importance of the effects of composition and wage structure in the job market. In the second, to verify which socioeconomic variables explain the effects of composition and wage structure in the job market. The information in this study was obtained from the microdata of Pesquisa Nacional por Amostra de Domicílios (PNAD) regarding the respective years. In the first stage of the methodology we used: the index of income distribution Theil-T; the income gap decompositions proposed by Oaxaca (1973) and Blinder (1973); and Firpo et al. (2007). In the second stage we applied the RIF regression method (Recentered Influence Function) of Firpo et al. (2007). The results show that income inequality is higher among men than among women in the country. It was observed that the component of inequality between people of the same gender represented the largest share in the decomposition of income inequality between genders. It was found, in the decomposition of the average income, a downward trend of income gap, but the differential remains favorable to the men. We noticed that the impact of the composition effect in reducing the gap was offset by the positive effect of wage structure. Regarding the distribution quantis, income differential between genres appeared greater at the bottom, in the years 1976, 1987 and 2009; and at the top of the distribution, in 1996 featuring, respectively, the sticky floor and glass ceiling effects in Brazil. As for the decomposition of the RIF, it turns out that the composition effect assisted in the downfall of the income gap between 1976 and 2009, but was offset by the positive effect of the wage structure in quantis 10th, 50th, and 90th. The main socioeconomic variables influenced the drop in income gap were: the composition effect, the manual labor occupations, service sector and low-grade and high school, and the wage structure effect, schooling low and high experience professional and technical occupations and urban centers